THE EFFECT OF TRUST AND CUSTOMER ENGAGEMENT ON BUYING INTEREST OF PAKUAN UNIVERSITY STUDENTS IN THE TIKTOK SHOP APPLICATION - Siti Hidajati Ramdani; Yuary Farradia; Ade Said Yurcel (Institut Bisnis Nusantara, 2025)
The rapid development of internet technology in Indonesia has changed people's shopping behavior, especially through social commerce platforms such as TikTok Shop. Tiktok Shop is a platform where users can buy products from sellers who sell through Tiktok videos. This study aims to analyze the effect of trust and customer engagement on buying interest in TikTok Shop among Pakuan University students. The research method used is quantitative with associative research type. Data was obtained from distributing questionnaires to 100 respondents. Determination of the number of samples using the Slovin formula with a non-probality sampling method based on accidential sampling. The results of the study with multiple linear regression tests show that trust and customer engagement have a positive and significant effect on buying interest in Pakuan University students.